Time-Driven Activity-Based Costing Systems for Marketing Decisions - Park Yonpae; Jung Sungwoo; Jahmani Yousef (Studies in Business and Economics, 2019)
The activity-based costing (ABC) systems emerged as a management accounting innovation in the mid-1980s in response to dissatisfaction with traditional management accounting techniques and heightened international competition. Although ABC provides many advantages for managerial decision making, ABC tends to be outdated due to its limitations and is substituted by the time-driven activity-based costing (TDABC) systems. TDABC requires estimates of only two parameters: how much it costs per time unit of capacity to supply resources to activities and how much time it takes to perform each activity. TDABC allows incorporation of variation in the time demands made by different types of processes and consequently the representation of all possible combinations of activities that a process performs. This paper uses TDABC to calculate marketing costs and describes TDABC as a useful technique to reduce marketing resource costs and to support effective marketing decision making in various contexts such as marketing processes restructuring, marketing mix choices, customer profitability and price differentiation for customer classes.